The extracellular matrix glycoprotein tenascin‐X regulates peripheral sensory and motor neurones. (18th July 2018) - Aktar, Rubina; Peiris, Madusha; Fikree, Asma; Cibert‐Goton, Vincent; Walmsley, Maxim; Tough, Iain R.; Watanabe, Paulo; Araujo, Eduardo J. A.; Mohammed, Sahar D.; Delalande, Jean‐Marie; Bulmer, David C.; Scott, S. Mark; et al.
Abstract : Key points: Tenascin‐X (TNX) is an extracellular matrix glycoprotein with anti‐adhesive properties in skin and joints. Here we report the novel finding that TNX is expressed in human and mouse gut tissue where it is exclusive to specific subpopulations of neurones. Our studies with TNX‐deficient mice show impaired defecation and neural control of distal colonic motility that can be rescued with a 5‐HT4 receptor agonist. However, colonic secretion is unchanged. They are also susceptible to internal rectal intussusception. Colonic afferent sensitivity is increased in TNX‐deficient mice. Correspondingly, there is increased density of and sensitivity of putative nociceptive fibres in TNX‐deficient mucosa. A group of TNX‐deficient patients report symptoms highly consistent with those in the mouse model. These findings suggest TNX plays entirely different roles in gut to non‐visceral tissues – firstly a role in enteric motor neurones and secondly a role influencing nociceptive sensory neurones Studying further the mechanisms by which TNX influences neuronal function will lead to new targets for future treatment. Abstract: The extracellular matrix (ECM) is not only an integral structural molecule, but is also critical for a wide range of cellular functions. The glycoprotein tenascin‐X (TNX) predominates in the ECM of tissues like skin and regulates tissue structure through anti‐adhesive interactions with collagen. Monogenic TNX deficiency causes painful joint hypermobility and skin hyperelasticity, symptoms characteristic of hypermobility Ehlers Danlos syndrome (hEDS). hEDS patients also report consistently increased visceral pain and gastrointestinal (GI) dysfunction. We investigated whether there is a direct link between TNX deficiency and GI pain or motor dysfunction. We set out first to learn where TNX is expressed in human and mouse, then determine how GI function, specifically in the colon, is disordered in TNX‐deficient mice and humans of either sex. In human and mouse tissue, TNX was predominantly associated with cholinergic colonic enteric neurones, which are involved in motor control. TNX was absent from extrinsic nociceptive peptidergic neurones. TNX‐deficient mice had internal rectal prolapse and a loss of distal colonic contractility which could be rescued by prokinetic drug treatment. TNX‐deficient patients reported increased sensory and motor GI symptoms including abdominal pain and constipation compared to controls. Despite absence of TNX from nociceptive colonic neurones, neuronal sprouting and hyper‐responsiveness to colonic distension was observed in the TNX‐deficient mice. We conclude that ECM molecules are not merely support structures but an integral part of the microenvironment particularly for specific populations of colonic motor neurones where TNX exerts functional influences. Key points: Tenascin‐X (TNX) is an extracellular matrix glycoprotein with anti‐adhesive properties in skin and joints. Here we report the novel finding that TNX is expressed in human and mouse gut tissue where it is exclusive to specific subpopulations of neurones. Our studies with TNX‐deficient mice show impaired defecation and neural control of distal colonic motility that can be rescued with a 5‐HT4 receptor agonist. However, colonic secretion is unchanged. They are also susceptible to internal rectal intussusception. Colonic afferent sensitivity is increased in TNX‐deficient mice. Correspondingly, there is increased density of and sensitivity of putative nociceptive fibres in TNX‐deficient mucosa. A group of TNX‐deficient patients report symptoms highly consistent with those in the mouse model. These findings suggest TNX plays entirely different roles in gut to non‐visceral tissues – firstly a role in enteric motor neurones and secondly a role influencing nociceptive sensory neurones Studying further the mechanisms by which TNX influences neuronal function will lead to new targets for future treatment.